Fumonisin B1 regulates LDL receptor and ABCA1 expression in an LXR dependent mechanism in liver (HepG2) cells. (30th January 2021) - Abdul, Naeem Sheik; Chuturgoon, Anil A.
Abstract: The metabolic toxicity of Fumonisin B1 (FB1 ) converges at the accumulation of sphingoid bases and reduced ceramide levels. Several studies have alluded to a hypercholesterolemic endpoint after FB1 exposure, yet the molecular mechanisms remain elusive. Cell surface receptors are important regulators of cholesterol metabolism by regulating influx of lipids and efflux of cholesterol. Western blot analysis showed that FB1 elevates the expression of ABCA1 (a cholesterol efflux promoter) in an LXR dependent mechanism. We further highlight the potential role of PCSK9 in the degradation of LDL receptor. These data provide important evidence for the mechanism underlying hypercholesterolemia in FB1 treated models. The disruption of lipid homeostasis by FB1 is beginning to shift away from canonical ceramide synthase inhibition, and this changed perspective may shed light on diseases caused by dysregulated cholesterol metabolism such as cancer initiation and promotion. Graphical abstract: Image 1 Highlights: Fumonisin B1 (FB1 ) converges at the accumulation of sphingoid bases and reduced ceramide levels. FB1 dysregulates cholesterol metabolism in HepG2 liver cells. FB1 altered the levels of LDLR and ABCA1 protein without affecting membrane integrity in HepG2 cells. FB1 upregulated PCSK9 protein expression, decreased LDLR and inhibited cholesterol influx.